Managing electronic records - William Saffady. (ARMA International)
Contents: Concepts and issues -- Storage media for electronic recordkeeping -- File formates for electronic records -- Inventorying electronic records -- Retention schedules for electronic records -- Managing vital electronic records -- Managing electronic files and media.Includes index and glossary."Suggestions for further study" : p. 225-226.